Cellular Specificity of NF-κB Function in the Nervous System - Dresselhaus, Erica C.; Meffert, Mollie K. (Frontiers in Immunology, 2019)
Nuclear Factor Kappa B (NF-B) is a ubiquitously expressed transcription factor with key functions in a wide array of biological systems. While the role of NF-B in processes such as host immunity and oncogenesis has been more clearly defined, an understanding of the basic functions of NF-B in the nervous system has lagged behind. The vast cell-type heterogeneity within the central nervous system (CNS) and the interplay between cell-type specific roles of NF-B contributes to the complexity of understanding NF-B functions in the brain. In this review, we will focus on the emerging understanding of cell-autonomous regulation of NF-B signaling as well as the non-cell-autonomous functional impacts of NF-B activation in the mammalian nervous system. We will focus on recent work which is unlocking the pleiotropic roles of NF-B in neurons and glial cells (including astrocytes and microglia). Normal physiology as well as disorders of the CNS in which NF-B signaling has been implicated will be discussed with reference to the lens of cell-type specific responses.